Shared Decision-making in Emergency Life-sustaining Treatment - Jun WU; Shu LI (Yixue yu zhexue)
Shared decision-making (SDM) model has been widely recognized in the world, but its practice in China is still in the exploratory stage. SDM has a broad implementation prospect in emergency department, where patients with serious illness and their family members often face decisions on life-sustaining treatment. This article first introduces the current application status of SDM in emergency department at home and abroad, and analyzes the difficulties and challenges of implementing SDM in life-sustaining treatment in emergency department in China from the perspectives of medical system, workflow technology, ethics, policies, etc. Finally, improvement suggestions are proposed, mainly including optimizing the medical system, improving doctor-patient relationships, enhancing emphasis on SDM and implementation capabilities, constructing SDM models and decision-aid tools, strengthening interdisciplinary collaboration, and providing policy and legislative support, etc.